Circuit Models of Lossy Multic onductor Transmission Lines: Incident Plane Wave Effect - Saih Mohamed; Rouijaa Hicham; Ghammaz Abdelilah (Institute of Advanced Engineering and Science, 2016)
In this paper, we concentrate on the variety impacts of incident plane wave on multiconductor transmission lines, utilizing Branin’s method, which is alluded to as the method of characteristics. The model can be directly used for the time-domain and frequency-domain analyses, Moreover, it had the advantage of being used without the need of setting the preconditions of the charges applied to its ends; this permits it to be effortlessly embedded in circuit simulators, for example Spice, Saber, and Esacap. This model validity is affirmed by contrasting our simulation results under ESACAP and different results, and we will talk about variety impacts of incident plane wave.